2005
DOI: 10.1086/444424
|View full text |Cite
|
Sign up to set email alerts
|

Breast‐Milk Shedding of Drug‐Resistant HIV‐1 Subtype C in Women Exposed to Single‐Dose Nevirapine

Abstract: Single-dose nevirapine reduces intrapartum human immunodeficiency virus 1 type (HIV-1) transmission but may also select for nonnucleoside reverse-transcriptase inhibitor (NNRTI) resistance in breast milk (BM) and plasma. Among 32 Zimbabwean women, median 8-week postpartum plasma and BM HIV-1 RNA levels were 4.57 and 2.13 log(10) copies/mL, respectively. BM samples from women with laboratory-diagnosed mastitis (defined as elevated BM Na(+) levels) were 5.4-fold more likely to have HIV-1 RNA levels above the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 12 publications
4
36
1
Order By: Relevance
“…Our findings confirm previous studies reporting high frequencies of drug-resistant virus in breast milk of NVP-SD-exposed pregnant women infected with HIV-1 [13][14][15]. Additionally, we found that most of the detected resistance mutations were present as minor drug-resistant variants accounting for <5% of the total viral population.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings confirm previous studies reporting high frequencies of drug-resistant virus in breast milk of NVP-SD-exposed pregnant women infected with HIV-1 [13][14][15]. Additionally, we found that most of the detected resistance mutations were present as minor drug-resistant variants accounting for <5% of the total viral population.…”
Section: Discussionsupporting
confidence: 91%
“…Different mutation patterns in breast milk and plasma is a consistent finding [13,14,23]. Furthermore, HIV-1 mutation patterns can also differ between samples from the right and left breast of the same women [14]. While it has been shown that a short-course of combivir (zidovudine and lamivudine) over 1 week can prevent the formation of NVP resistances in plasma after NVP-SD intake [24], it is not known whether this holds true for other compartments, that is, for breast milk.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…143 Around half the women who received one dose of nevirapine to prevent mother-to-child transmission harbour viruses resistant to non-nucleoside reverse transcriptase inhibitors (NNRTI). 144,145 These resistant viruses replicate efficiently and can be transmitted by breast milk, 146 and minor resistant populations present long after the intervention can possibly decrease the effectiveness of subsequent NNRTI-based treatment regimens. 147 The combination of short-course zidovudine, lamivudine, and nevirapine prevents peripartum transmission while reducing the risk of nevirapine resistant viruses.…”
Section: Drug Resistancementioning
confidence: 99%